Student Progress Reporting System for RehabNPlay Therapy Centre - Baharuddin, Nurul Ain Melissa (2025)
Student Progress Reporting System for RehabNPlay Therapy Centre (SPRS) is a webbased system to record student progress and manage therapy sessions. Monitoring the growth and progress of disability students need commitment. This project identified that the manual process in managing student progress reports, inconsistent student progress tracking, and inadequate platform to communicate student progress with parents in current business process. To address this issue, SPRS is the consideration of using web technology using Adapted Waterfall Model which includes six sequential and iteration between phases, which are planning, analysis, design, implementation, testing, and documentation. During the planning phase of development, three objectives were established to overcome the problems in the therapy reporting process faced by RehabNPlay Therapy Centre. Besides that, Shneiderman's eight golden rules are used to design user interface. These rules as a guideline for designing interfaces of SPRS. The system consists of three users, therapists, parents, and administrative staff. Therapists can record and update student progress, manage therapy sessions, and response to parents' feedback. Parents can view their child's progress, give feedback, and download the student performance report. Administrative staff manage user accounts, oversee program data, and monitor overall system activity. To guarantee quality, the functionality and usability of SPRS is carried out with test plan and tested by three experts. All the feedback and suggestions from experts are used to improve the SPRS. To conclude, the SPRS was designed to be a centralized student progress reporting process. The results of the testing show that SPRS implementation aligned with the theory chosen but still needs some improvements.